THE CONCEPT OF INFORMATION AND COGNITIVE ENVIRONMENT AS A METHODOLOGICAL BASIS OF THE FUTURE TEACHERS’ PROFESSIONAL TRAINING IN THE CONDITIONS OF THE HIGHER EDUCATIONAL INSTITUTION’S ACTIVITIES - Krasiuk Iryna; Udris Iryna (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2022)
The article studies the issue of creation and productive functioning of the educational environment of a higher education institution, which is a resource in the formation of the future teachers’ professional competence and the creative activity style as essential characteristics of the pedagogical professionalism. The article aims to reveal the possibilities of the information and cognitive environment in the person’s professional formation and to substantiate the conceptual provisions of using its resources to ensure the quality of future teachers’ professional preparation for professional activities. The methods of analysis, modelling and interpolation of the environmental approach provisions to the construction of the informational and cognitive environment of the higher pedagogical education institution have been applied in the study. It has been shown, the information and cognitive environment is a set of conditions that ensure the productivity of future teachers’ professional and creative growth based on the use of various information sources and cognitive technologies that stimulate students’ mastery by professional competences, the development of their cognitive abilities and readiness to apply the resource opportunities of pedagogical design in creating an atmosphere of scientific research, working up of original programs and projects, the creative performance of professional functions. The functions of the informational and cognitive environment have been characterized. Among them: integrative function, which contributes to the influence of all environmental circumstances on the coordination of actors’ goals, motives, attitudes, aspirations and ways of interaction in the educational process; value-formative function, which is aimed at the formation of professional and pedagogical values; interactive function, which is ensuring the interrelation of the capabilities of the educational subjects and pedagogical design in creating a positive emotional atmosphere and psychological comfort; developmental function, which is aimed at shaping a creative activity style, and educational and upbringing function providing conditions for the formation the future teachers’ informational and cognitive readiness for productive pedagogical activity. The possibilities of the event-role situation have been established. It has been shown, an event-role situation is an important unit of the environment, a reserve for improving the quality of the educational process in the university and training competitive specialists for the pedagogical area capable of creative professional pedagogical activity. The pedagogical terms for the productivity of the information and cognitive environment in establishing emotionally favourable circumstances and psychological comfort for the development of students’ professional abilities, creative thinking, active professional position and a creative style of activity, have been reasoned. It has been emphasized that the factors of future teachers’ professional development are the guidance on professional and personal evolution, active participation in professionally orientated event-role situations and the educational dialogue as means of pedagogical interaction, cooperation and co-creation. It has been concluded that the information and cognitive environment affects the quality of the implementation of new requirements for pedagogical professionalism in the university education system, the formation of the main characteristics of the future teachers’ professional competence including its conceptual, instrumental, integrative, contextual, adaptive aspects and the ability for the interpersonal communication.